Reformasi Birokrasi Sebagai Upaya Mewujudkan Good Governance Melalui Kerangka Otonomi Daerah - Rifi Rivani Radiansyah (Universitas Islam Malang, 2020)
Bureaucratic reform which initially existed to support the success of regional autonomy, in practice often creates inconsistency problems which actually give birth to paradoxes. So it happened in West Bandung Regency. On the other hand, the bureaucracy improves itself through the implementation of bureaucratic reform, but on the other hand it slows down the progress of the bureaucracy with the practice of corruption. This paper aims to find out the problems of bureaucratic reform and to find out whether the implementation of bureaucratic reform has shown optimal results in West Bandung Regency. This paper review uses qualitative methods through empirical normative-juridical approach and institutional theory approach. Data collection is done by official document collection techniques. Data analysis techniques in this study were carried out using interpretive descriptive methods. The results of the study in this paper show that the bureaucratic reform carried out by the West Bandung regency government through the practice of regional autonomy has not shown signs that are more optimal in the effort to realize Good Governance. Normatively, this condition is caused by the still low quality (competency) of apparatus resources, accompanied by other things that are mimetic and coercive which also influence the apparatus mentality as a whole based on their interests such as the influence of leadership, culture and the bureaucratic environment.